Triage of women with a positive HPV DNA test: evaluating a DNA methylation panel for detecting cervical intraepithelial neoplasia grade 3 and cervical cancer in cervical cytology samples - Yifei Ren; Fengjiang Qin; Li Shen; LanFang Li; Qingrong Wu; Ping Yi (BMC Cancer)
Abstract Background Efficient triage of high-risk human papillomavirus (hrHPV)-positive women is essential to avoid unnecessary referrals and overtreatment. This study evaluates the diagnostic accuracy of the commercially available DNA methylation panel, GynTect® (ASTN1, DLX1, ITGA4, RXFP3, SOX17, and ZNF671), in cervical cytology samples from 146 women for detecting cervical intraepithelial neoplasia grade 3 (CIN3) or cervical carcinoma (CC). This analysis focuses particularly on the performance of the ZNF671 methylation marker (ZNF671m) within the panel. Results The positive rates of all triage markers—hrHPV, TCT, HPV16/18, GynTect®, and ZNF671m—correlated with increasing severity of CIN lesions (Chi-squared test for trend, P < 0.01). ZNF671m exhibited the highest Area Under the Curve (AUC) of 0.811 (95% CI: 0.734–0.888) for identifying CIN3 + cases, closely followed by GynTect® (AUC 0.800, 95% CI: 0.721–0.878). Among 102 hrHPV-positive women, employing GynTect® or ZNF671m instead of TCT yielded identical sensitivity (0.84; 95% CI: 0.69–1.01) but enhanced specificity (86% and 90%, respectively) for detecting CIN3 +. Adding HPV16/18 to the triage strategy maintained similar outcomes. Additionally, ZNF671m showed a significant risk difference (60.0%; 95% CI 42.8–77.1%) for detecting CIN3 +, on par with GynTect® (57.6%; 95% CI 37.9–71.2%). Conclusion ZNF671m within the GynTect® panel demonstrates robust triage performance in diagnosing CIN3 + cases, with efficacy comparable to the full panel. These findings suggest that ZNF671m could be a promising alternative for cytologic triage, warranting further validation.